THEORETICAL-LEGAL SIGNIFICANCE OF THE PRINCIPLE OF SOCIAL JUSTICE IN INTERNATIONAL LAW (World Bulletin of Management and Law, 2025)
This article highlights the theoretical legal significance of the principle of social justice in the constitutional law of developed countries in international law, including the fact that the advantages of the principle of social justice in the legislation of those countries are also applied in the legislation of the Republic of Uzbekistan